Effect of Hormonal Supplementation on Pain Tolerance in Women, A Cross Sectional Study - Marryam Riaz, Shazia Sukhera, Naghmana Lateef, Jawaria Ilyas, Varda Balouch, Madiha Akram, Farhat Ijaz (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Hormonal supplementation (Oestrogen and progesterone) significantly influence pain sensitivity in women. Neuropathic pain prevention and nociceptive actions are strongly affected by progesterone and oestrogen. The present study aimed to investigate the gonadal hormones on women’s pain sensation. Materials and Method: this case-control study was conducted on 46 females (study group) on the combined oral contraceptive pill (COCP) and 46 healthy males (control group) at the Department of Physiology, Lahore General Hospital, Lahore from November 2020 to July 2021. As a stimulus source, a cold pressor test was used. The participant’s least dominant hands were placed in a water bath with a temperature between 0◦C and 2◦C and were instructed to notify when the pain was first sensation feel which represents the pain threshold of participants. Pain tolerance was referred to the duration from the initial threshold to a stage where pain severity increased beyond the participant’s coping with pain. A visual analog scale was set to measure the unpleasantness and pain intensity. SPSS version 23 was used for data analysis. The Chi-square test was used, and p values less than 0.05 were considered significant. Results: Pain tolerance and unpleasantness was not significantly differ in men and women taking combined oral contraceptive pill. However, women on combined oral contraceptive pill had significantly higher (p<0.001) pain tolerance on average scale. Average pain threshold had insignificant association with age. Comparing to naturally menstruating women the unpleasantness pain on average scale was less severe in women taking hormonal pills. The average pain intensity was considerably differ between women on COCP pills and normal women. Conclusion: Our study suggests that gonadal hormone levels changes had a lower effect on experimental pain and unpleasantness in women. COCP influence the average pain reported by participants. Upon comparing normal and women on COCP pills, a significant increase in pain tolerance was observed in females on pill therapy. Women utilizing hormonal contraceptives should be kept under supervision for unpleasant and severe pain.